The effective power output of the Taurus 301 blood warmer when warming small volume units of red cell concentrate described using simulated blood products - Eave, Dylan (Department of Anaesthesia and Perioperative Medicine, 2024)
Background and Literature review At Groote Schuur Hospital, the lead anaesthesiologist in the cardiothoracic team, J. Ozinsky, identified the need for a device capable of warming blood rapidly prior to transfusion. Such a device was subsequently developed as a collaborative effort between the Department of Anaesthetics and Department of Electrical Engineering at the University of Cape Town. The device became known as the “Taurus” blood warmer, namesake of the Head of Department at the time, and clinical leader of the project, Prof. A.B. Bull. A subsequent version of the Taurus, which warms blood within the bag in which it is packaged, remains in active clinical service at Groote Schuur Hospital. Literature search reveals that devices which employed electromagnetic radiation for warming of blood and blood products were met with resistance following many case reports of haemolysis induced by warming. A common theme identified was that of elevated risk of haemolysis, due to local overheating, in blood products of high haematocrit (HCT) and small volume. The Taurus 301 performance has been evaluated extensively and the device used for over 30 years. Without any literature available to suggest that the device is overtly harmful it may be concluded that the device design is one that may be drawn upon with confidence especially for these blood products at elevated risk of haemolysis. The Taurus range of blood warmers represent the only examples of a radio-frequency blood warmers that were made available commercially for clinical use. In 1996 fire swept through the factory responsible for manufacture of Taurus blood warmers. Taurus manufacturing capability was not restored and more than a quarter century has now passed since the last Taurus 301 was commissioned. Taurus devices may still be found in active service within some South African hospitals.(1) The author has also observed the scrapping of at least 3 units from the Groote Schuur Hospital Complex over the past 5 years and, if the situation parallels that of other hospitals, the Taurus may soon be lost to clinical practice. Research questions The mean effective power output of the Taurus 301, when used for the warming of small volume units of red cell concentrate, in the setting of massive transfusion, prior to this study, was unknown. The primary aim of this study was to describe the mean effective power output of the Taurus 301 in this context. To realise this aim, four identical bags of simulated, small volume, red cell concentrate were prepared and cooled to 4 oC before being warmed sequentially using a Taurus 301 which remains in active service. For each warming instance calorimetry was used to determine effective power output of the device. The bags were thereafter again cooled to 4 oC and 24 such warming instances undertaken. It was also unknown whether or not the increase in effective power output observed for bags warmed serially, in the Taurus 301, is significant. The secondary aim of this study was to determine the extent and significance of this increase. This secondary aim was achieved by means of subgroup analysis in which comparison was made between effective power output 11 observed for bags warmed as a function of sequence within a batch of serial warming instances. Methods For the purposes of evaluating the warming performance of an electromagnetic blood warming device, concentrations of saline may be used to simulate the electrical properties of specific blood products. The interaction between blood and electromagnetic radiation has been exhaustively studied and these data made available. Perusal of these data will reveal, among other properties, the conductivity of blood for a range of haematocrit values, temperatures and electromagnetic field frequencies. Using these data, and that of saline solutions, a saline-based blood product simulation is possible. The experiment was conducted within a laboratory adjacent to the main theatre complex at 2 Military Hospital, a tertiary-level hospital in Cape Town, South Africa, where there remains a functional Taurus 301 blood warmer. This particular Taurus 301 is functional and used regularly for the warming of red cell concentrates. Four simulated bags of red cell concentrate of small volume served as subjects for the experiment. These four bags underwent cycles of cooling and then warming, using the Taurus 301. Results The Taurus 301 mean effective power output, when considering all warming instances, was 172.04 W (n = 96; 95% CI 169.61 – 174.47). A mean effective power output of 153.11 W (n=24; 95% CI 151.37 – 154.85) and 181.61 W (n=24; 95% CI 179.95 – 183.26) was observed when warming the first bag and last bag in each batch respectively. Taurus maximum power output was thus seen to be observed during warming of the last bag in a batch. When considering the difference in effective power output between bags warmed first and those warmed subsequently, a statistically significant increase in mean power of 25.25W (p <0.001; 95% CI 23.00 to 27.49) was observed. Conclusion This research has determined the mean maximum effective power output of Taurus 301, when used to warm the most vulnerable of blood product units, to be 181.61 W (n=24; 95% CI 179.95 – 183.26), and makes this value known in the interests of providing insight into what is likely a safe power output target for a prototype modernised Taurus.